2007
DOI: 10.1593/neo.07397
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NAD(P)H:Quinone Oxidoreductase By Radiation Potentiates the Effect of Bioreductive β-Lapachone on Cancer Cells

Abstract: We found that beta-lapachone (beta-lap), a novel bioreductive drug, caused rapid apoptosis and clonogenic cell death in A549 human lung epithelial cancer cells in vitro in a dose-dependent manner. The clonogenic cell death caused by beta-lap could be significantly inhibited by dicoumarol, an inhibitor of NAD(P)H:quinone oxido-reductase (NQO1), and also by siRNA for NQO1, demonstrating that NQO1-induced bioreduction of beta-lap is an essential step in beta-lap-induced cell death. Irradiation of A549 cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
76
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 34 publications
14
76
1
Order By: Relevance
“…In good agreement with previous reports (Boothman et al, 1993;Planchon et al, 1995Planchon et al, , 2001Wuerzberger et al, 1998;Pink et al, 2000;Park et al, 2005a;Suzuki et al, 2006;Choi et al, 2007;Song et al, 2008), we have observed in the present study that not only the apoptosis and clonogenic cell death caused by β-lap but also the synergistic interaction between β-lap and irradiation in causing cell death occurred preferentially in the NQO1-positive A549 cells relative to NQO1-null shNQO1 A549 cells (Figure 1). These results clearly demonstrated that the effect of β-lap and NQO1 activity is closely related.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In good agreement with previous reports (Boothman et al, 1993;Planchon et al, 1995Planchon et al, , 2001Wuerzberger et al, 1998;Pink et al, 2000;Park et al, 2005a;Suzuki et al, 2006;Choi et al, 2007;Song et al, 2008), we have observed in the present study that not only the apoptosis and clonogenic cell death caused by β-lap but also the synergistic interaction between β-lap and irradiation in causing cell death occurred preferentially in the NQO1-positive A549 cells relative to NQO1-null shNQO1 A549 cells (Figure 1). These results clearly demonstrated that the effect of β-lap and NQO1 activity is closely related.…”
Section: Discussionsupporting
confidence: 94%
“…The cells were stained with propidium iodide (PI, Sigma) and apoptosis was assessed using the FACSCalibur flow cytometer (Beckman Dickinson) (Choi et al, 2007).…”
Section: Apoptosis Analysismentioning
confidence: 99%
See 3 more Smart Citations